Analyzing the Intersection of Labor Market Dynamics and Economic Growth: A Bibliometric Study - Judijanto, Loso; Supriyanto, Supriyanto; Supriandi, Supriandi (West Science Interdisciplinary Studies, 2024)
This study conducts a bibliometric analysis to examine the intersection of labor market dynamics and economic growth, focusing on key themes, trends, and emerging areas of research. Using VOSviewer, we analyze 980 publications from 1959 to 2024, identifying central themes such as "labour market," "human capital," and "economic development," which play critical roles in shaping the relationship between workforce dynamics and economic growth. The findings highlight how technological advancements, globalization, and demographic shifts have influenced labor market structures, wage dynamics, and industry-specific developments over time. Emerging topics, such as the relationship between labor markets and energy consumption, point to the growing importance of sustainability in economic discussions. The results provide valuable insights into the evolution of labor market studies and offer directions for future research, particularly in the context of green energy transitions and workforce adaptability in an age of rapid technological change. This analysis contributes to a more comprehensive understanding of the complex interactions between labor market behavior and economic performance.